'Harvesting a participatory movement' - Anika Rice (Thomas A. Lyson Center for Civic Agriculture and Food Systems, 2021)
The Jewish Farmer Network (JFN) is a North American grassroots organization that mobilizes Jewish agricultural wisdom to build a more just and regenerative food system for all. This paper presents methodological findings and reflections from the initial stages of a participatory action research (PAR) collaboration led by the authors and JFN organizers centered on Cultivating Culture, JFN’s inaugural conference in February 2020. For this early iterative phase, we used a PAR approach to guide event ethnography to both facilitate and understand collective movement building and action. This work included pre-conference collaborative research design, a participatory reflection and action workshop with roughly 90 participants, evaluative surveys, short ethnographic interviews, and ongoing post-conference analysis with researchers and movement organizers. While this data was first analyzed and organized for JFN’s use, we present findings to demonstrate the effectiveness of foregrounding event ethnography within a PAR research design at an early stage of movement formation, especially how elements of event ethnography can address some of the limitations of using PAR with a nascent network of farmers. Our work revealed themes in the movement of Jewish farming: the politics of identity in movement building, the tensions around (de)politicization, and the production of Jewish agroecological knowledge. We reflect on the utility of using PAR to frame scholar-activism and propose future inquires for Jewish agrarianism.